KAJIAN PERTUMBUHAN PENDAPATAN ASLI DAERAH KABUPATEN/KOTA SE JAWA TENGAH PERIODE 2008-2012 - Akuarista, Arum; N. Masdjojo, Gregorius (Proceeding SENDI_U, 2015)
This study aims to analyze the influence of Regional Expenditure, Gross Regional Product, andInvestment to the Local Revenue in Central Java Province during the period 2008-2012. Thedata used in this study is a secondary data including Regional Expenditure, Gross DomesticProduct, Investment, and Local Revenue from the 35 District / City in Central Java on the period2008-2012. Based on Haussman test, then the data was analysed by Fixed Effect Model (FEM)based on panel data multiple regression analysis method. This research found that theExpenditure has no significant effect to the Local Revenue. Gross Regional Product andInvestment have significant positive effect on the Local Revenue.Keywords: Regional Expenditures, Gross Regional Product, Investment, Local Revenue, FixedEffect Model (FEM, Random Effect Model (REM).